Survival Rate of Tribolium Beetles When Exposed to Extreme Diets - Stewart, Nathan; Marshall, Jeremy (My University, 2017)
This research project was set up to determine the suitability of two extreme diets. Since this experiment only used basic extremes, some of the data were already known, or assumed, such as that a flour beetle can survive on a diet of wheat flour (Imura, 1991). In more detailed experiments on this subject, artificial diets can be made for more accurate data, as well as temperature regulation (Romo, 2016). Diet formulation for flour beetles is largely assumed to be just flour. However, the exact components of the diet, such as protein, carbohydrates, fatty acids, and other factors are never really taken into consideration unless testing exact diets specifically. By testing different levels of these factors in diets, we can raise beetles for testing more efficiently (Maner, 2013). I would like to see if any beetles will survive off of a food with no nutritional value, and if there will be enough nutrition for the beetles to start reproduction in any of the jars. This experiment showed that having nutritious food allows for greater survival than a food with no nutritional value. The small amount of good nutrients even allows for the start of reproduction of the beetles, while none was observed in the poor diet. The results from this experiment show the extremes of insect diets, and that it is important to create a good diet formula to ensure the proper growth and development of experimental insect colonies. By continuing testing of different diets, the process of rearing insects can become much more efficient.
Citation: Stewart, N. (2017). Survival Rate of Tribolium Beetles When Exposed to Extreme Diets . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.